Anti-inflammatory effect of conditioned medium from human uterine cervical stem cells in uveitis. (August 2016) - Bermudez, Maria A.; Sendon-Lago, Juan; Seoane, Samuel; Eiro, Noemi; Gonzalez, Francisco; Saa, Jorge; Vizoso, Francisco; Perez-Fernandez, Roman
Abstract: The aim of the present study was to evaluate the effect of conditioned medium from human uterine cervical stem cells (CM-hUCESCs) in uveitis. To do that, uveitis was induced in rats after footpad injection of Escherichia coli lipopolysaccaride (LPS). Human retinal pigment epithelial (ARPE-19) cells after LPS challenge were used to test anti-inflammatory effect of CM-hUCESCs 'ìn vitro'. Real-time PCR was used to evaluate mRNA expression levels of the pro-inflammatory cytokines interkeukin-6, interkeukin-8, macrophage inflammatory protein-1 alpha, tumor necrosis factor alpha, and the anti-inflammatory interkeukin-10. Leucocytes from aqueous humor (AqH) were quantified in a Neubauer chamber, and eye histopathological analysis was done with hematoxylin-eosin staining. Additionally, using a human cytokine antibody array we evaluated CM-hUCESCs to determine mediating proteins. Results showed that administration of CM-hUCESCs significantly reduced LPS-induced pro-inflammatory cytokines both 'in vitro' and 'in vivo', and decreased leucocytes in AqH and ocular tissues. High levels of cytokines with anti-inflammatory effects were found in CM-hUCESCs, suggesting a possible role of these factors in reducing intraocular inflammation. In summary, treatment with CM-hUCESCs significantly reduces inflammation in uveitis. Our data indicate that CM-hUCESCs could be regarded as a potential therapeutic agent for patients suffering from ocular inflammation. Highlights: An evaluation of the therapeutic effect of conditioned medium from human uterine cervical stem cells on uveitis is made. CM-hUCESCs significantly reduces inflammation in uveitis. Potential use of CM-hUCESCs for patients suffering inflammatory ocular diseases.